Quality of Life and Self-Esteem Among Diabetic Patients in Jordan - Tashtoush, Rami; Al-Kechar, Mohammed (Jordan Journal of Educational Sciences, 2017)
This study aimed to reveal the quality of life and self-esteem levels and the relationship between them among diabetics in Jordan. The sample of the study consisted of (360) male and female diabetic patients type II. To achieve the aims of the study, the researchers used the World Health Organization Quality of Life and Rosenberg’s self-esteem scale. Results revealed a high level on both of life quality and self-esteem for diabetic patients, and statistically significant differences in the quality of life due to the variables of gender, educational qualification, and the duration of the disease. While there were no statistically significant differences in the quality of life due to the variable of age. Also, the results of the study showed that there are statistically significant differences in the self-esteem due to the variables of gender and educational qualification. While there were no statistically significant differences in self-esteem due to the variables of age and the duration of the disease. Finally, the study showed statistically positive relationship between quality of life and self-esteem